EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ON PREVENTION OF ICU DELIRIUM AMONG NURSES - Ashwini; Prabhu, Savitha; Shetty, Sushmitha; Prabhu, Veena; Pais, Maria; Kuriakose, Basil (Journal of Health and Allied Sciences NU, 2015)
Delirium is extremely common in intensive care unit (ICU) patient due to comorbidity, critical illness and iatroogenesis. This complication of hospital stay is extremely hazardous in older persons and is associated with prolonged hospital stays. yet ICU nurses and physicians are usually unaware of the presence of hypoactive delirium and only recognize this disturbance in agitated patients (hyperactive delirium).The aim of the study was to assess the existing knowledge of ICU staff nurses regarding ICU delirium and to assess the effectiveness of structured teaching programme on the knowledge of ICU staff nurses regarding ICU delirium. An evaluative approach with one group Pretest Posttest design was used for the study. Fourty samples were selected by using non-probability purposive sampling method, in selected hospitals of Udupi District. The collected data were analyzed using descriptive and inferential statistics. A significant difference between Pretest and Posttest knowledge was found (t=23.95, p=<0.0001). The study findings showed that there significant increase in posttest knowledge of ICU staff nurses regarding ICU delirium. The nurse can identify the delirium early and prevent the complication by treating well in advance.
Keywords: Knowledge questionnaire; structured teaching program (STP)